NorMAD - Maizatul Nurhuda, bt. Saadon; Mohamad Faizuan, bin Mat; Noorhaslina, binti Senin; Siti Shahida, Kamel; Mohamad Zamhari, bin Abolhassan (2018)
This research focuses on the exploration and experimenting of High - Density Polyethylene (HDPE) plastic waste as material for home decoration design. Labelled as No. 2 plastic, it is typically found in plastic bags and refillable plastic bottles. It has the nature of lightweight, malleable, weather resistance and is considered a low hazard plastic. Not known to leach any chemicals that are suspected of causing cancer or disrupting hormones. Many recycled HDPE is used to manufacture lawn and garden products, buckets, crates , office products and automotive parts. Thus this research tries to explore the potential of this material as in home decoration design.In addition, this research could solve the problem of disposal of solid waste.